2011
DOI: 10.2135/cropsci2010.08.0465
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Diverse Maize Inbred Line Collection and its Potential Utilization for Stress Tolerance Improvement

Abstract: ReseaRch It is predicted that cereal production will need to rise to over 400 million t by 2050 to meet the demands, which represents an increase in yield of 37% from current values (Tester and Langridge, 2010). However, this is a challenge, especially for smallholders and resource-poor farmers, most of whom grow maize (Zea mays L.) on marginal lands with low inputs and constant exposure to a variety of abiotic (drought, low N, acid soils, waterlogging, and heat) and biotic (pests, diseases, and weeds) stresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 61 publications
(72 reference statements)
9
43
1
Order By: Relevance
“…Pedigree analysis placed 119 inbred maize lines into eight and SSR markers resulted in clustering the inbred lines into 10 groups (Reid et al, 2011). Similar results were reported by Wen et al (2011) where nine main subsets were clustered using pedigree information.…”
Section: Genetic Distancesupporting
confidence: 73%
“…Pedigree analysis placed 119 inbred maize lines into eight and SSR markers resulted in clustering the inbred lines into 10 groups (Reid et al, 2011). Similar results were reported by Wen et al (2011) where nine main subsets were clustered using pedigree information.…”
Section: Genetic Distancesupporting
confidence: 73%
“…Best eleven hybrids selected simultaneously based on grain yield (GY, Mg ha grain yield over maximizing heterosis and yield potential in final (commercial) three-way hybrids; therefore, use of lines from three different heterotic groups should be advantageous for meeting both objectives. On the other hand, in a study using a diverse panel of tropical and subtropical lines from CIMMYT and IITA stress tolerance breeding programs, Wen et al (2011) found considerable genetic variation within the existing CIMMYT heterotic groups A and B. Therefore, reclassification of working germplasm in CIMMYT breeding programs using methods such as molecular-marker-determined GDs and SCA analysis followed by the discriminant analysis of principal components (Jombart et al, 2010), as described herein, can be practical and effective in developing heterotic groups for further development and use in breeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…Maize plants were grown as part of the CIMMYT field trials, in which a collection of 300 hybrid lines representing the genetic diversity within the CIMMYT and International Institute of Tropical Agriculture tropical and subtropical maize improvement programs (Wen et al, 2011) were tested for tolerance to DS, HS, and DS+HS . Ten maize experimental hybrids (Table I) were chosen to cover a wide range of drought and heat tolerance on grain yield observed in previous field trials .…”
Section: Grain Yield Was Affected By Stress Treatmentsmentioning
confidence: 99%
“…While direct selection for grain yield under DS has resulted in admirable gains in grain yield under stress (Bänziger et al, 2006;Cairns et al, 2013), further improvement requires the incorporation of additional selection traits (Cairns et al, 2012a(Cairns et al, , 2012b. In recent years, genetic and phenotypic markers have been searched extensively for drought tolerance of maize by high-throughput genomic and phenotyping approaches, respectively (Tuberosa and Salvi, 2006;Wen et al, 2011;Araus et al, 2012;Cairns et al, 2013;Prasanna et al, 2013;Araus and Cairns, 2014;Tsonev et al, 2014). Moreover, metabolic markers started to draw attention due to their close relationship with yield phenotypes (Fernie and Schauer, 2009;Redestig et al, 2011;Riedelsheimer et al, 2012aRiedelsheimer et al, , 2012bWitt et al, 2012;Degenkolbe et al, 2013).…”
mentioning
confidence: 99%